Peningkatan Kapasitas Kelompok Wanita Tani Desa dalam Pemanfaatan Limbah Sawit Sebagai Silase - Gustria Ernis; Nola Windirah; Ahmad Saleh Harahap (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
Massive land conversion into palm oil tree plantation causes massive plantation waste (palm fronds) and the decrease of animal food in Jenggalu Village, Sukaraja, Seluma, Bengkulu. The solution for the problem is by utilizing palm fronds as silage (fermented animal food). The purpose of this community service is to improve the ability of female farmer group (Kelompok Wanita Tani/ KWT) Tanjung Aur in utilizing palm fronds as silage. The method applied is theory and practice on how to create silage, preparing the procedure to create silage along with the main ingredients, and then holding the workshop on processing food fermentation from palm fronds using EM-4 activator. To maintain the continuity of the program, besides choosing the person in charge of the equipment, a supervision was also done in the form of monitoring and evaluation. After the fermentation process is completely applied for the livestock, the obtained results indicate that cows really like the food, this can be seen from the consumption increase. From the observation, the animal food and its technology are categorized as ‘useful’ and ‘very useful’ based on KWT members’ understanding. From the activity, it can be concluded that the KWT members’ ability towards the technology of utilizing palm fronds as silage is improved and it will be continuously applied.